UPAYA PENINGKATAN KUALITAS PRODUK DAN CITRA PRODUK MELALUI PENCIPTAAN KEPUASAN UNTUK MEMBANGUN KOMITMEN PELANGGAN (Studi Empiris pada Perusahaan Batik Kaibon di Kabupaten Pekalongan) (Students' Journal of Economic and Management, 2013)
The purpose of this study was to analyze the quality of the product that has a positive effect on the creation of customer satisfaction, to analyze the image of the product that has a positive effect on the creation of customer satisfaction, to analyze the quality of the product that has positive influence on customer commitment, to analyze the image of the product that has positive influence on customer commitment and to analyze that the creation of customer satisfaction has a positive effect on customer commitments. Object of this study is the company's customers in the District of Pekalongan Batik Kaibon with research methods using purposive sampling technique. Customers here are all Kaibon Batik enterprise customers with the criteria already made a purchase more than 2 times that used either alone or given to someone else as a gift. Regression analysis equations I know the coefficient of determination or ajusted R square of 0.665. This means that the influence of the independent variable is the quality of the product and the image of the product to customer satisfaction is of 66.5% or in other words the variation changes in customer satisfaction able to be explained by the quality of the product and the image of the product by 66.5%, while the remaining 33,5% is influenced by other variables not examined. The regression analysis equation II is known coefficient of determination or ajusted R square of 0.712. This means that the influence of the independent variable is the quality of the product, the product image and customer satisfaction to customer commitments amounted to 71,2% or in other words the variation changes in customer commitment that can be explained by the variable quality of the product, the product image and customer satisfaction by 71,2%, while the remaining 28,8% is influenced by other variables not examined. The results were analyzed variable product quality, brand image, customer satisfaction and customer commitment showed that the quality of the product, the product image and customer satisfaction has a positive and significant impact on customer commitment variables, This shows that the higher the effect of each independent variable is product quality, product image and customer satisfaction, the customer will be higher commitment. Keywords: product quality, product image, customer satisfaction and customer commitment.